PTU-109 Development of a gastroenterology-led patient-centred service for neuroendocrine tumours(NETS) in wales:population-based national commissioning. (8th June 2018) - Khan, Mohid Shakil; Reynolds, Mark; Bell, Carole; Hopps, Rebecca; Powell, Catherine; Morgan, Carys; Gwynne, Sarah; Rees, Dafydd Aled; Christian, Adam
Abstract : Introduction: Requiring many specialities, NETs have complex pathways presenting a challenge to plan services in existing NHS structures. In Wales, we aimed to produce patient-centred services for Neuroendocrine Tumours (NETs) incorporating the addition of specialist gastroenterology services to endocrinology, oncology and surgery across Wales by government-assisted population based commissioning. Methods: WHSSC (Welsh Health Specialised Services Committee) coordinated a group of patient representatives, clinicians, nurses and planners to evaluate existing services in Wales and to make recommendations for a gastroenterology-led service. Options were appraised by the national cancer network, disease experts, 2 ENETS centres of excellence and patients/relatives. Results: The existing service demonstrated inequalities across healthcare boundaries. Patient surveys suggested little nurse specialist input, inconsistent feedback from multidisciplinary meetings (MDM), and lack of access to specialist expertise. Recommendations included funding 2 specialist nurses, appropriate central MDM staffing, leadership and appropriate expertise with some diagnostics and treatments delivered locally. Policies for Gallium 68 -PET imaging and peptide receptor radionuclide therapy (PRRT) were developed. Eight NHS health boards/trusts, 17 acute hospitals were involved. North Wales patients were served by the Liverpool NET service due to geography. In a short space of time, the NET MDT has been transformed, with accurately coded real-time records and timely communication to referring clinicians across the region. The addition of expertise from a gastroenterologist trained in a centre of excellence improved quality of life (QoL). With the focus on QoL, an app to monitor wellbeing remotely has been developed. Two appointed specialist nurses are undergoing tailored training and are accessible to patients regardless of geography. Patients have access to a specialist clinic based in Cardiff with a smaller hub in Swansea. Using a nationwide digital health record (Welsh Clinical Portal), communication with referring teams has improved including use of imaging and pathology close to the patients home saving on travel for patients. Feedback from patients and clinicians, has been vigorously positive including positive patient stories. Conclusions: In this complex cancer/chronic disease, care has been transformed across organisational boundaries on a national basis through listening to individuals and groups and an emphasis on quality of life. Ongoing development continues to ensure sustainability and excellence.